Parental education and income are linked to offspring cortical brain structure and psychopathology at 9-11 years - Linn B. Norbom; Jaroslav Rokicki; Espen M. Eilertsen; Thea Wiker; Jamie Hanson; Andreas Dahl; Dag Alnæs; Sara Fernández‐Cabello; Dani Beck; Ingrid Agartz; Ole A. Andreassen; Lars T. Westlye; et al. (Wiley, 2024)
Abstract Background A child's socioeconomic environment can shape central aspects of their life, including vulnerability to mental disorders. Negative environmental influences in youth may interfere with the extensive and dynamic brain development occurring at this time. Indeed, there are numerous yet diverging reports of associations between parental socioeconomic status (SES) and child cortical brain morphometry. Most of these studies have used single metric‐ or unimodal analyses of standard cortical morphometry that downplay the probable scenario where numerous biological pathways in sum account for SES‐related cortical differences in youth. Methods To comprehensively capture such variability, using data from 9758 children aged 8.9-11.1 years from the ABCD Study®, we employed linked independent component analysis (LICA) and fused vertex‐wise cortical thickness, surface area, curvature and grey‐/white‐matter contrast (GWC). LICA revealed 70 uni‐ and multimodal components. We then assessed the linear relationships between parental education, parental income and each of the cortical components, controlling for age, sex, genetic ancestry, and family relatedness. We also assessed whether cortical structure moderated the negative relationships between parental SES and child general psychopathology. Results Parental education and income were both associated with larger surface area and higher GWC globally, in addition to local increases in surface area and to a lesser extent bidirectional GWC and cortical thickness patterns. The negative relation between parental income and child psychopathology were attenuated in children with a multimodal pattern of larger frontal‐ and smaller occipital surface area, and lower medial occipital thickness and GWC. Conclusion Structural brain MRI is sensitive to SES diversity in childhood, with GWC emerging as a particularly relevant marker together with surface area. In low‐income families, having a more developed cortex across MRI metrics, appears beneficial for mental health.